Peran Ibu Rumah Tangga dalam Membentuk Keluarga Sakinah Mawaddah Warrohmah di Desa Gedung Jaya Negara Batin Way Kanan - Duri, Afika; Irhamudin, Irhamudin; As’ari, Hasyim As’ari (Attractive : Innovative Education Journal, 2024)
A sakinah, mawaddah, warahmah family is a family that is peaceful and peaceful, happy, loves each other and is full of affection. In the Sakinah family, mutual respect and appreciation is very important. Being loyal to your partner and living in harmony can keep your family in harmony and intact. Based on and guided by the Al-Qur'an and Hadith, it will lead to achieving a sakinah, mawaddah and warahmah family. A sakinah, mawaddah, warahmah family is a family that obeys Allah SWT. This type of research is descriptive qualitative. The data sources used are primary and secondary. Data collection tools use observation, interviews and documentation methods. Based on the research results, it can be concluded that to form a family that is sakinah, mawaddah, warahmah, the role of a housewife who is qualified in all aspects and is able to become an educator for her children is really needed. By always being based on and guided by the Al-Qur'an and Hadith, because these two sources will be able to lead us to create a family that is sakinah, mawaddah, and warahmah and to get the blessing of Allah SWT. Keywords: The Role of a Housewife, Sakinah Mawaddah Warahmah